2013
DOI: 10.1016/j.juro.2012.09.116
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Organic Dietary Choice During Pregnancy and Hypospadias in Offspring: A Study of Mothers of 306 Boys Operated on for Hypospadias

Abstract: This large case-control study of boys operated on for hypospadias suggests an association between hypospadias in the offspring and the mother not choosing the organic alternative, and having a high current intake of nonorganic butter and cheese. This finding could be due to chemical contamination of high fat dairy products. However, general lifestyle and health behavior related to choosing organic alternatives may also explain the finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 25 publications
1
34
1
1
Order By: Relevance
“…No associations were seen for other organic food groups. The authors suggested as an explanation www.annualreviews.org • Exposure and Health Implicationsthat conventionally produced butter and cheese may contain more traces of pesticide residues than the organic equivalents, but they did not have measurements to support this (23).…”
Section: Reproductive Anomalies In Boysmentioning
confidence: 99%
See 3 more Smart Citations
“…No associations were seen for other organic food groups. The authors suggested as an explanation www.annualreviews.org • Exposure and Health Implicationsthat conventionally produced butter and cheese may contain more traces of pesticide residues than the organic equivalents, but they did not have measurements to support this (23).…”
Section: Reproductive Anomalies In Boysmentioning
confidence: 99%
“…The studies included end points ranging from atopy, eczema, and/or respiratory disease (3,4,60,98,104) to reproductive anomalies in boys, (19,23), preeclampsia (106), sperm quality (1,54,57,62), cancer (15), and risk factors for cardiovascular disease (30). All except one study were observational.…”
Section: Health Benefits Linked To Organic Food Consumptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have examined diet as a potential source of exposure to Endocrine disruptive chemicals (EDCs). Maternal choice of an organic alternative to food items during pregnancy was not associated with a decreased risk of hypospadias in the offspring [80].…”
Section: Diet and Pesticidesmentioning
confidence: 86%